Using Artificial Intelligence to Forecast Stock Markets - Rauhala, Viljo-Verneri (My University, 2025)
This thesis examines the application of AI in stock market forecasting by comparing the per-formance of several AI-based models to traditional forecasting approaches. The study evalu-ates how AI models, such as Support Vector Machine (SVM), Artificial Neural Network (ANN) and Long Short-Term Memory (LSTM) can overcome the limitations of traditional models, which often rely on assumptions of market efficiency, linearity, and rational investor behav-iour. These assumptions frequently fail in modern, volatile, and non-linear financial environ-ments. This thesis concludes that AI is not just a supportive technology but a critical component in the evolution of stock market forecasting and portfolio management. AI models enable real-time adaptability and improved decision-making in environments characterized by uncertain-ty and rapid change. As financial markets continue to evolve, the integration of AI with do-main knowledge and alternative data sources will shape the next generation of intelligent financial systems.

Tässä tutkielmassa tarkastellaan tekoälyn soveltamista osakemarkkinoiden ennustamiseen vertaamalla useiden tekoälypohjaisten mallien suorituskykyä perinteisiin ennustamismenetelmiin. Tutkimuksessa arvioidaan, kuinka tekoälymallit, kuten tukivektorikone (SVM), tekoälyneuroverkko (ANN) ja pitkäkestoinen lyhytaikainen muisti (LSTM), voivat ylittää perinteisten mallien rajoitukset, jotka usein perustuvat oletuksiin markkinoiden tehokkuudesta, lineaarisuudesta ja sijoittajien rationaalisesta käyttäytymisestä. Nämä oletukset eivät useinkaan päde nykyaikaisissa, epävakaissa ja epälineaarisissa rahoitus ympäristöissä. Tässä tutkielmassa päätellään, että tekoäly ei ole vain tukeva teknologia, vaan kriittinen komponentti osakemarkkinoiden ennustamisen ja salkunhallinnan kehityksessä. Tekoälymallit mahdollistavat reaaliaikaisen sopeutumiskyvyn, paremman päätöksenteon epävarmuuden ja nopeiden muutosten leimaamissa ympäristöissä. Rahoitusmarkkinoiden kehittyessä edelleen tekoälyn integrointi alan tietämykseen ja vaihtoehtoisiin tietolähteisiin muokkaa seuraavan sukupolven älykkäitä rahoitusjärjestelmiä.
Keywords: machine learning; artificial intelligence; forecasts; stock prices; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|